PENDEKATAN HERMENEUTIK DALAM PENEGAKAN HUKUM (UPAYA DEKONSTRUKSI TERHADAP POSITIVISME HUKUM) - Hermansyah, Hermansyah (Jurnal Dinamika Hukum, 2009)
Law enforcement is one of great problem in our development country. Law itself; often misused by agent of law enforcement, likely police, attorneys even judge. If it’s traced, that the beginning problem is the strong of positivism as paradigm in life of law, where the law itself only as state of law where the interpretation of law stressing on certainty only. Hermeneutics, especially critical hermeneutic, an offered in law enforcement. Kata Kunci: Penegakkan hukum, positivism dan hermeneutik